S67. Corticomuscular coherence in childhood dystonia. (May 2018) - McClelland, Verity M.; Cvetkovic, Zoran; Lin, Jean-Pierre; Mills, Kerry
Abstract : Introduction: There is growing evidence of abnormal sensorimotor processing in idiopathic and genetic dystonias.Mechanisms may differ in patients with secondary/acquired dystonias, but there are few physiological studies in this group.Corticomuscular coherence (CMC) quantifies synchrony between oscillatory EEG and EMG activity and reflects bidirectional cortex-muscle interaction.Beta range CMC is modulated by sensory stimuli..Several studies show elevated 3–7 Hz intermuscular coherence (IMC) in myoclonus dystonia or DYT1 dystonia.Neither IMC or CMC have been studied in acquired dystonia.This study aimed to record CMC/IMC in children with genetic/idiopathic and acquired dystonia, and to assess its modulation by afferent stimuli. Methods: 16 children with dystonia and 13 typically developing children (TDC) participated (age 12–18 yrs).The child grasped a 15 cm ruler between thumb and index finger of the dominant hand.Mechanical perturbations to the ruler were provided by an electromechanical tapper.Surface EMG was recorded from First dorsal interosseous (FDI) and forearm extensors (FEx).Bipolar scalp EEG was recorded over contralateral sensorimotor cortex.Up to 200 5-s epochs of data were collected per subject.EMG and EEG signals were amplified, bandpass filtered (EEG 0.5–100 Hz; EMG 5–250 Hz) and sampled at 1024 Hz.Coherence was calculated for EEG:FDI, EEG:FEx and FDI:FEx using a short-time Fourier transform giving a frequency resolution of 2 Hz.95% confidence levels for significant coherence were calculated for each child.Bonferroni correction was applied to maintain type I error level at 0.05.The 500 ms window was moved across the 5-s data epoch in 50 ms steps to assess CMC/IMC change over time.CMC/IMC was compared between baseline, early (0.5–2 s) and late (2.0–3.5 s) post-stimulus periods using Fisher transformed coherency and Student t -test.Findings were compared between groups. Results: Significant beta range (14–36 Hz) CMC and IMC was detected post-stimulus in all children, but was seen more consistently in the TDCs.An adult pattern of beta CMC/IMC modulation (McCelland et al., 2012 ) was seen in 10/13 TDCs versus only 4/16 children with dystonia (all acquired).For the TDC group, beta-CMC for combined FDI:EEG and FEx:EEG increased significantly from baseline to the early post-stimulus period ( p = 0.015), returning to baseline in the late post-stimulus period.For the genetic and acquired dystonia groups the beta-CMC in the post-stimulus period was not significantly increased from baseline.For IMC, the change from baseline to early post-stimulus was significant for both the TDC ( p = 0.003), and the acquired dystonia group ( p = 0.047) but not the genetic/idiopathic dystonia group( p = 0.088). Conclusion: Beta range CMC can be identified in children with dystonia but both its magnitude and its modulation by sensory stimulation are less consistent than in TDCs. The findings also suggest differences in CMC/IMC between genetic/idiopathic vs acquired dystonia.